MEMBIDIK PASAR OBAT ANTISEPTIK: ANALISIS FAKTOR YANG MEMPENGARUHI INTENSI PEMBELIAN KEMBALI PRODUK - Helman Arif; Andreina Fara (Unitri Press, 2020)
This study aims to analyze what factors underlie consumer decisions to repurchase antiseptic products in Indonesia. Specifically, the analysis is carried out on variables perceived as risk, perceived price, brand image, brand awareness, subjective norms, and experience that are associated with trust and brand attitude to form repurchasing intention. The study was conducted using a survey method in two years with different data sets of consumers, each with 126 and 114 respondents. The testing was done by regression method. The analysis is then added to the results of focus group discussions (FGD). It was concluded that all research variables proved to influence the intention to repurchase an antiseptic product, however, there was a shift in the order of importance of a factor or variable in which the brand attitude variable became increasingly important while perceived risk and experience became increasingly unimportant.